A false mirror - Todd, Charles (New York : William Morrow, 2007)
A love triangle turned deadly sends Scotland Yard Inspector Ian Rutledge to Hampton Regis, a small harbor town that simmers with secrets. Accused of beating the husband of a woman who jilted him, Rutledge's former trenchmate takes her hostage to escape arrest, and he demands Rutledge prove his innocence.
Keywords: Police -- England -- Fiction; Detective and mystery fiction